Brain Activity Changes in Slow 5 and Slow 4 Frequencies in Patients With Optic Neuritis: A Resting State Functional MRI Study - Yan, Kai; Shi, Wen-Qing; Su, Ting; Liao, Xu-Lin; Wu, Shi-Nan; Li, Qiu-Yu; Yu, Jing; Shu, Hui-Ye; Zhang, Li-Juan; Pan, Yi-Cong; Shao, Yi (Frontiers in Neurology, 2022)
Objective We used the amplitude of low-frequency fluctuation (ALFF) method to investigate spontaneous brain activity in patients with optic neuritis (ON) in specific frequency bands. Data and Methods A sample of 21 patients with ON (13 female and eight male) and 21 healthy controls (HCs) underwent functional magnetic resonance imaging (fMRI) scans in the resting state. We analyzed the ALFF values at different frequencies (slow-4 band: 0.027–0.073 Hz; slow-5 band: 0.01–0.027 Hz) in ON patients and HCs. Results In the slow-4 frequency range, compared with HCs, ON patients had apparently lower ALFF in the insula and the whack precuneus. In the slow-5 frequency range, ON patients showed significantly increased ALFF in the left parietal inferior and the left postcentral. Conclusion Our results suggest that ON may be involved in abnormal brain function and can provide a basis for clinical research.